Homework's Implications for the Well-Being of Primary School Pupils-Perceptions of Children, Parents, and Teachers - Iasmina Negru; Simona Sava (MDPI AG, 2023)
Teachers and educational researchers explore various approaches to make homework more engaging and enjoyable, intending to improve the well-being and academic performance of primary school students. The study aimed to identify practices with positive and negative effects on students' well-being when doing homework. The views of those involved in giving, doing, and assessing homework were captured from three perspectives, namely, teachers, students, and parents. In May-June 2022, six online focus groups were conducted with the participation of 13 teachers, 11 parents, and 16 primary school students from a Romanian school. The thematic analysis identified the homework that the children (do not) like; their reactions when they receive, do, and are assessed for such homework; and suggestions on how to improve the homework. The results revealed that homework assignments that make young schoolchildren feel capable, effective, appreciated, and rewarded; homework done in teams in the form of competitions or games; parental involvement in collaborative homework; and homework with creative elements are effective ways that contribute to the well-being of primary school pupils when doing homework. Repetitive, lengthy, tedious, overloaded homework generates frustration, discouragement, and emotional reactions such as crying, abandonment, anxiety, and sleep deprivation.